Medical Adhesive–Related Skin Injury Prevalence at the Peripherally Inserted Central Catheter Insertion Site: A Cross-sectional, Multiple-Center Study. Issue 1 (January 2018) - Zhao, Huihan; He, Yu; Wei, Qin; Ying, Yanping
Abstract : PURPOSE: We examined prevalence and associated risk factors of medical adhesive–related skin injury (MARSI) at the peripherally inserted central catheter (PICC) insertion site in hospitalized oncology patients in Guangxi, China. DESIGN: A cross-sectional, multiple-center epidemiological study. SUBJECTS AND SETTING: The sample comprised 697 adult inpatients at 4 tertiary hospitals (3 general hospitals and 1 oncology hospital). The facilities are located in the western China. METHODS: Trained nurses examined and assessed all subjects' skin exposed to medical adhesive during PICC maintenance process followed by recording the morphological features of the skin lesions, complaints of the patients, and information of catheter maintenance. Data related to patient demographics, PICC insertion information, disease, and laboratory parameters were collected through the electronic medical record. The prevalence of MARSI was calculated statistically and risk factors were examined using a logistic regression model. RESULTS: A total of 697 patients (mean age, 48.86 years; range, 18-89 years) were enrolled. The prevalence of MARSI was 19.7% (137/697), including mechanical skin injury 5.0% (35/697), contact dermatitis 14.8% (103/697), folliculitis 1.0% (7/697), and moisture-associated skin damage 1.3% (9/697). There were significant differences in presence of MARSI and age, diagnoses, body mass index, smoking history, indwelling time of PICC, types of dressing, types of antiseptic, a history of MARSI, and skin allergies ( P < .05). Multivariate analysis identified 50 years or older (odds ratio [OR], 2.202; 95% confidence interval [CI], 1.222-3.968; P = .009), a history of MARSI (OR, 14.834; 95% CI, 6.534-33.680; P = .000) as independent risk factors for MARSI. Additionally, type of transparent film dressing used was a risk factor for MARSI (OR, 3.292; 95% CI, 1.092-9.923; P = .034). CONCLUSION: The prevalence of MARSI is significant in hospitalized oncology patients in China. Our study provided new knowledge for the epidemiology of MARSI and identified high-risk population, which will guide clinical nursing practice and ensure patient safety.